2020
DOI: 10.1002/jlb.4ma0120-115rr
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular adenosine enhances the ability of PMNs to kill Streptococcus pneumoniae by inhibiting IL-10 production

Abstract: Polymorphonuclear leukocytes (PMNs) are crucial for initial control of Streptococcus pneumoniae (pneumococcus) lung infection; however, as the infection progresses their persistence in the lungs becomes detrimental. Here we explored why the antimicrobial efficacy of PMNs declines over the course of infection. We found that the progressive inability of PMNs to control infection correlated with phenotypic differences characterized by a decrease in CD73 expression, an enzyme required for production of extracellul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(76 citation statements)
references
References 74 publications
5
71
0
Order By: Relevance
“…We previously found that PMNs were key determinants of disease during primary pneumococcal pneumonia and are required to initially control bacterial numbers (20,79). In this study we found that aging was associated with earlier influx of PMNs into the lungs of co-infected mice.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We previously found that PMNs were key determinants of disease during primary pneumococcal pneumonia and are required to initially control bacterial numbers (20,79). In this study we found that aging was associated with earlier influx of PMNs into the lungs of co-infected mice.…”
Section: Discussionsupporting
confidence: 52%
“…that IL-10 impairs PMN anti-bacterial function by inhibiting ROS production in response to infection(79). Blocking this cytokine boosted PMN anti-bacterial function and importantly restored resistance of vulnerable hosts to primary pneumococcal pneumonia(79).In summary, here we modified existing murine models to establish an experimental system that reflects the transition of S. pneumoniae from asymptomatic colonizer to invasive pulmonary pathogen upon IAV co-infection. In this model, IAV triggers the transition of a pathobiont from a commensal to a pathogenic state through modification of bacterial behavior in the nasopharynx, enhancement of bacterial colonization in the lung, and compromise of PMN-mediated anti-bacterial immunity.…”
mentioning
confidence: 99%
“…Mice that lacked CD73 suffered dramatically higher pulmonary bacterial numbers, systemic spread of the infection, and increased lethality upon S. pneumoniae lung infection (Bou Ghanem, Clark, Roggensack, et al, 2015). Importantly, CD73 controlled PMN antimicrobial activity (Siwapornchai et al, 2020). CD73 expression and EAD production by PMNs was required for their ability to kill and clear S. pneumoniae (Siwapornchai et al, 2020).…”
mentioning
confidence: 99%
“…Importantly, CD73 controlled PMN antimicrobial activity (Siwapornchai et al, 2020). CD73 expression and EAD production by PMNs was required for their ability to kill and clear S. pneumoniae (Siwapornchai et al, 2020).…”
mentioning
confidence: 99%
“…IL-10 participates in the inflammatory response by inhibiting the bactericidal ability of polymorphonuclear leukocytes (PMN). If IL-10 is blocked, the ability to kill pathogenic microorganisms is enhanced (Siwapornchai et al, 2020). Furthermore, IL-10 is considered an immunosuppressive cytokine, which promotes tumor immune escape by reducing the anti-tumor immune responses in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%